(untitled) (AmeriQuests)
Recent political events across the United States and Europe have shaken the international community. A weakened European Union, the presidential election of Donald Trump, and widespread anti-immigration sentiment indicate a decrease in support and enthusiasm for international cooperation. Countries have turned their focus inward and are emphasizing border protection and national interests above all else, at the expense of broader international concerns. The geopolitical landscape is marked by anxiety and uncertainty, as the bonds of the global community seem increasingly fragile. The nature of today’s political climate led me to Stefan Zweig’s autobiography, The World of Yesterday (1964).